Hubungan Implementasi Sistem Informasi Manajemen Rumah Sakit (SIMRS) dengan Kinerja Perawat - Hamdan Ramadhani; Retno Issroviatiningrum; Dyah Wiji Puspita Sari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The computer-based Hospital Management Information System (SIMRS) is a tool that supports and plays an important role in managing hospital operations. In the SIMRS regulations regulated in the Minister of Health of the Republic of Indonesia Regulation Number 82 of 2013 article 2, the aim of the SIMRS regulations is stated, namely, to improve efficiency, effectiveness, professionalism, performance, as well as hospital access and services. The participation of nurses in providing good hospital services will determine the success of health services. This research aims to determine the relationship between the implementation of the Hospital Management Information System and the performance of nurses at the Sultan Agung Islamic Hospital, Semarang. This research uses quantitative research with a cross-sectional approach. Data collection used a questionnaire using 100 respondents. This research uses a total sampling technique and is processed statistically with the correlation test used in this research, namely the chi square test. So from the chi square test of Hospital Management Information System (SIMRS) data with nurse performance, a p value of 0.000 (<0.05) was obtained, which shows that Ha is accepted or there is a fairly strong relationship and closeness (0.468) and the direction of the relationship is positive. There is a relationship between the implementation of the Hospital Management Information System and Nurse Performance.